BASLAWÍSH TÁLIM ANA TILI SABAQLARÍNDA OQÍWSHÍLARDÍ ERKIN PIKIRLEW HÁM DÓRETIWSHILIKKE ÚYRETIW - Konısbayeva, G.Sh. (SCIENCE and SOCIETY, 2023)
This article presents the methods of teaching students to independent thinking in the lessons of the native language in classes, modern technologies in teaching, their connection with other disciplines, ideas on how to increase the effectiveness of teaching.